2013
DOI: 10.1371/journal.pone.0053595
|View full text |Cite
|
Sign up to set email alerts
|

Nuisance Ecology: Do Scavenging Condors Exact Foraging Costs on Pumas in Patagonia?

Abstract: Predation risk describes the energetic cost an animal suffers when making a trade off between maximizing energy intake and minimizing threats to its survival. We tested whether Andean condors (Vultur gryphus) influenced the foraging behaviors of a top predator in Patagonia, the puma (Puma concolor), in ways comparable to direct risks of predation for prey to address three questions: 1) Do condors exact a foraging cost on pumas?; 2) If so, do pumas exhibit behaviors indicative of these risks?; and 3) Do pumas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 44 publications
3
48
0
Order By: Relevance
“…This was likely due to our methods rather than the ecological reality of the system, and a more intensive field effort may have yielded different results (Knopff et al 2010;Elbroch and Wittmer 2013b). Because we employed the night > 1 model to quantify kill rates, we limited our ability to detect small prey or large prey when large competitors displaced cougars from their kills (Elbroch and Wittmer 2013a). This would influence both our comparison of selection for smaller ungulates and the predictive power of our kill rate models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was likely due to our methods rather than the ecological reality of the system, and a more intensive field effort may have yielded different results (Knopff et al 2010;Elbroch and Wittmer 2013b). Because we employed the night > 1 model to quantify kill rates, we limited our ability to detect small prey or large prey when large competitors displaced cougars from their kills (Elbroch and Wittmer 2013a). This would influence both our comparison of selection for smaller ungulates and the predictive power of our kill rate models.…”
Section: Discussionmentioning
confidence: 99%
“…We expected summer cougar kill rates to increase because of a shift from larger (elk) to smaller (mule deer) prey (Knopff et al 2010). We expected winter cougar kill rates to increase because of greater wolf presence at cougar kills (Bartnick et al 2013), forcing cougars to abandon their kills more quickly and therefore to hunt more frequently (sensu Elbroch and Wittmer 2013a). Finally, we summarized cause-specific cougar mortality data over the full course of the study.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps pumas follow rules of optimal foraging theory (MacArthur and Pianka 1966), and abandon carcasses like ''patches'' in v www.esajournals.org marginal value theorem (Charnov 1976), when the benefits of remaining with the carcass diminish to a yet undetermined tipping point (Carbone et al 2005, Vucetich et al 2012. Research from Patagonia revealed that scavenging condors increased puma kill rates by reducing puma handling time at carcasses (Elbroch and Wittmer 2013a), and Murphy (1998) proposed similar effects due to scavenging bears in North America. The influence of kleptoparasitism on other carnivore foraging ecology has also been well documented in wolves and African wild dogs (Gorman et al 1998, Carbone et al 2005, Kaczensky et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Kill rates, defined as the numbers of prey killed per individual predator per unit time (Holling 1959), are possibly the most fundamental component of ecology required for modeling predator-prey dynamics (e.g., Lotka-Volterra equations;Lotka 1925, Volterra 1926. Estimates of kill rates have increased our understanding of dynamic species interactions in complex multispecies communities, including apparent competition affecting rare prey (Holt andLawton 1994, Wittmer et al 2013), predation-mediated Allee effects (McLellan et al 2010), and the effects of kleptoparasitism on the fitness of subordinate competitors (Gorman et al 1998, Elbroch andWittmer 2013a). Accurate estimates of kill rates are also essential for managers charged with setting sustainable harvest quotas for game species coexisting with native predators (e.g., White and Lubow 2002), and developing conservation strategies for species negatively affected by predation, including those in reintroduction programs (e.g., Rominger et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…However, because carnivores are constrained by gut capacity, solitary carnivores can only maximize their caloric yield by repeatedly returning to feed on a prey carcass. In developed habitats, carnivores can be particularly vulnerable to risk-foraging trade-offs because disturbance-induced carcass abandonment can result in food loss owing to scavenging [17] or decomposition [18]. Prey consumption time can therefore be limited by external forces that reduce carnivore access to a carcass.…”
Section: Introductionmentioning
confidence: 99%